THE EFFECT OF DEPOSITS AND NON-PERFORMING LOANS ON BANK PROFITABILITY: (Case Study on Conventional Commercial Banks listed on the Indonesia Stock Exchange for the period 2015 - 2021) - Nur Rokhmat; Sri Zulaihati; Santi Susanti (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2023)
This study aims to examine the effect of deposits and non-performing loans on bank profitability. The population in this study were conventional commercial banks listed on the Indonesia Stock Exchange during the observation period, namely from 2015 – 2021. After using a purposive sampling technique to select the sample, 41 sample data were chosen. The type of data in this research is unbalanced panel data. The analysis technique in this study is panel data regression with the selected regression model being the fixed effect model. The results of testing the hypothesis stated that partially savings had an effect but not significant on bank profitability. Meanwhile, non-performing loans have a significant effect on profitability. Simultaneously, savings and non-performing loans have a significant effect on profitability.